2021
DOI: 10.1073/pnas.2104008118
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the mechanisms controlling heme supply and demand

Abstract: In addition to heme’s role as the prosthetic group buried inside many different proteins that are ubiquitous in biology, there is new evidence that heme has substantive roles in cellular signaling and regulation. This means that heme must be available in locations distant from its place of synthesis (mitochondria) in response to transient cellular demands. A longstanding question has been to establish the mechanisms that control the supply and demand for cellular heme. By fusing a monomeric heme-binding peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 67 publications
(99 reference statements)
1
21
0
Order By: Relevance
“…Free heme (either ferrous or ferric) is envisaged as being present in minuscule concentrations but will still represent a mechanism for heme to be made available in cells. 77 In (C), chaperone-mediated heme delivery to an apo -heme protein (pale red circle), for example by GAPDH. 113 115 In (D), heme bound to heme-binding partners (dark gray pacman) constitutes a body of exchangeable heme readily available for downstream applications, in the same way as in (B).…”
Section: The Logistics Of Heme Supply and Demandmentioning
confidence: 99%
See 3 more Smart Citations
“…Free heme (either ferrous or ferric) is envisaged as being present in minuscule concentrations but will still represent a mechanism for heme to be made available in cells. 77 In (C), chaperone-mediated heme delivery to an apo -heme protein (pale red circle), for example by GAPDH. 113 115 In (D), heme bound to heme-binding partners (dark gray pacman) constitutes a body of exchangeable heme readily available for downstream applications, in the same way as in (B).…”
Section: The Logistics Of Heme Supply and Demandmentioning
confidence: 99%
“…An ability to store heme in cells would decrease the reliance of cells on heme synthesis and degradation and could be coupled to mechanisms to make heme more or less available, on-demand and at speed ( Figure 3 D). To date, there have been no proteins identified that have the dedicated function of storing heme, but there is evidence, from recent work, 77 of a buffering capacity within cells that can accommodate changes in either the total concentration of heme (i.e., [ H t ]), or the concentration of exchangeable heme (i.e., [ H e ]), while maintain the capability to mobilize heme as and when necessary. As indicated above, it is entirely possible that known heme proteins (such as indoleamine 2,3-dioxygenase, and GAPDH) participate in the buffering of free heme concentration ([ H f ]) and protect the cell against increases or decreases in total, or exchangeable, heme concentration.…”
Section: The Logistics Of Heme Supply and Demandmentioning
confidence: 99%
See 2 more Smart Citations
“…To promote PBG accumulation, we had to limit the activity of subsequent PBG-consuming reactions toward porphyrins. Since porphyrin biosynthesis is essential for cell survival, knocking out any of these PBG-consuming reactions would be lethal (Mobius et al 2010 ) (Leung et al 2021 ). Hence, we applied Clustered Regularly Interspersed Short Palindromic Repeats interference (CRISPRi) (Qi et al 2013 ) to repress the expression of hemC , whose encoding gene product of HemC mediates the conversion of PBG to HMB, with minimal impact to cell physiology.…”
Section: Introductionmentioning
confidence: 99%